Method for extracting tanshinone IIA from radix salviae miltiorrhizae - XU LI; SU XUEHUI; WAN LI; LI YUWEI; YAO DEKUN (2018)
The invention belongs to the technical field of traditional Chinese medicine extraction, relates to a method for purifying tanshinone IIA, and particularly relates to a method for extracting tanshinone IIA from radix salviae miltiorrhizae. By applying supercritical CO2 fluid extraction, original color and flavor can not be damaged by heating, heat sensitivity can be better ensured, and substanceswhich are easy to oxidize can not be damaged; and extracts can also be simultaneously separated and purified in the extraction process. The method provided by the invention has the advantages that macroporous adsorption resin which is stable in physicochemical property, larger in surface area, higher in exchange speed, high in mechanical strength, high in anti-pollution capability and good in heatstability is selected, and the macroporous adsorption resin is insoluble in acids, alkalis and organic media, has better selectively to organic substances, is free from influence of inorganic salts and strong-ion low-molecula